2014
DOI: 10.3322/caac.21245
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and evaluating shared decision making in oncology practice

Abstract: Engaging individuals with cancer in decision making about their treatments has received increased attention; shared decision making (SDM) has become a hallmark of patient-centered care. Although physicians indicate substantial interest in SDM, implementing SDM in cancer care is often complex; high levels of uncertainty may exist, and health care providers must help patients understand the potential risks versus benefits of different treatment options. However, patients who are more engaged in their health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
161
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(182 citation statements)
references
References 83 publications
(116 reference statements)
2
161
0
2
Order By: Relevance
“…Low health literacy and high emotions impede the understanding of information. Demands on providers limit the time they can spend with any one patient, 45 and what the physician communicates and what the patient hears and remembers can differ greatly. 11,31,46,47 Furthermore, physician training has historically not included communication skills, though this may be beginning to change.…”
Section: Sources Of Information Before Hctmentioning
confidence: 99%
See 3 more Smart Citations
“…Low health literacy and high emotions impede the understanding of information. Demands on providers limit the time they can spend with any one patient, 45 and what the physician communicates and what the patient hears and remembers can differ greatly. 11,31,46,47 Furthermore, physician training has historically not included communication skills, though this may be beginning to change.…”
Section: Sources Of Information Before Hctmentioning
confidence: 99%
“…11,31,46,47 Furthermore, physician training has historically not included communication skills, though this may be beginning to change. 45 It is a challenging setting for clear dialogue between the patient/family and the members of their treatment team.…”
Section: Sources Of Information Before Hctmentioning
confidence: 99%
See 2 more Smart Citations
“…This may reflect differences across demographic subgroups and patients' presenting complaints. For instance, a review of SDM in oncology concluded that, overall SDM is associated with better outcomes and greater patient satisfaction, however there may be variability across patient groups and cancer types with respect to how involved patients want to be in decision-making processes [16].…”
Section: Introduction (Revised)mentioning
confidence: 99%